Breast Magnetic Resonance Imaging and Its Impact on the Surgical Treatment of Breast Cancer - Georgia Tsina; Philippe Simon (Hindawi Limited, 2014)
Breast MRI focuses on the detection of multifocality, multicentricity, and bilaterality of newly diagnosed breast cancer. A retrospective study was carried out on 833 patients that were diagnosed and treated for breast cancer between January 2002 and December 2011. Patients were divided into two groups: those that had a presurgery breast MRI and those that did not. The two groups were compared on the basis of the several parameters. The aim of the study was to determine whether the use of MRI in breast cancer screening changes the initial treatment decision. In 18% of the patients, MRI revealed a multifocal or a multicentric unilateral breast cancer, a bilateral tumour, or a larger cancer than initially diagnosed. Most of these patients underwent a second-look breast ultrasound, with or without an additional biopsy. The percentage of mastectomies did not increase as a result of an MRI exam. Neoadjuvant chemotherapy was used more often and the percentage of reoperations decreased when an MRI was performed.